Local Phage Therapy During Surgical Treatment of Burn Wounds Reduces the Risk of Colonization of the Skin of the Periwound Area by Pathogens of the ESKAPE Group - V. V. Beschastnov; A. A. Tulupov; M. G. Ryabkov; I. E. Pogodin; O. V. Kovalishena; I. Yu. Shirokova; E. V. Dudareva; N. A. Belyanina; K. V. Andryuhin; E. F. Badikov (Неотложная медицинская помощь)
Aim of study To study the effect of local phage therapy alone and in combination with systemic antibiotic therapy on the dynamics of microflora colonizing the skin of the periwound area during surgical treatment of infected burn wounds.Material and methods Scientific hypothesis: the use of local phage therapy in monotherapy in the treatment of burn wound infections reduces the risk of colonization of the skin of the periwound area by bacteria of the ESKAPE group. The experimental study analyzed the results of microbiological studies of washings from the skin surface of 40 animals with infected burn wounds, in the course of phage therapy in monotherapy and in combination with systemic antibiotic therapy.Results In the group of animals receiving phage therapy alone, the proportion of ESKAPE group bacteria colonizing the skin of the periwound area at the time of completion of the course of antimicrobial therapy was 9%, while in the group receiving phage therapy in combination with systemic antibiotic therapy it was 43% (p=0.011).Conclusion The use of local phage therapy in single mode during the surgical treatment of infected burn wounds reduces the risk of colonization of the skin of the peri-wound area by pathogens of the ESKAPE group. At the same time, systemic antibiotic therapy causes an imbalance of resident and transient skin microbiota in the periwound area and an increase in the frequency of its colonization by pathogens of the ESKAPE group.